Development of neutron survey meter using prescila neutron probe - Luong Thi, Hong; Nguyen Tien, Phong; Pham Thi, Bich; Nguyen Du, Huyen (Nuclear Science and Technology, 2018)
This paper presents the design and validation of a neutron survey meter. The meter consists of a PRESCILA neutron probe (with good sensitivity, directional response, gamma rejection, and enhanced high-energy response to 20 MeV) and an electrometer developed at Non-Destructive Evaluation center. The homogeneity response of the PRESCILA neutron probe was investigated as a function of distances from the 241Am - 9Be source in order to obtain the appropriate distance for accurate count-rate measurements using the neutron survey meter. A system consists of the PRESCILA neutron probe and the Ludlum Model 2326 electrometer was then used for measuring neutron ambient dose equivalent rates in the range from 50 cm to 200 cm with the step of 25 cm. The relationship between the count-rates and neutron dose equivalent rates (in the distance ranged from 50 to 200 cm) were deduced to validate the proper operation of the neutron survey meter.